Perinatal Management of Bart's Hemoglobinopathy: Paradoxical Effects of Intrauterine, Transplacental, and Partial Exchange Transfusions - Curran, Mark; Mikhael, Michel; Sun, Wang-Dar; Lim, Jina; Leung, Anna; Morchi, Gira; Chmait, Ramen H. (American Journal of Perinatology Reports, 2020)
We describe a fetus at 24 3/7 weeks' gestation that showed ultrasound evidence of anemia, hydrops, and severe growth restriction. Both parents were known to be cis heterozygous carriers for SEA α-thalassemia deletion (αα/–). Cordocentesis confirmed fetal anemia and homozygous α-thalassemia (−/−) in the fetus. Fetal intrauterine transfusions corrected the anemia, treated the hydrops, and improved fetal growth. The postnatal course was complicated by hypoxic respiratory failure and persistent pulmonary hypertension of the newborn, which resolved only after partial volume exchange transfusion. This case report is presented to point out the potential unintended outcomes with transplacental transfusion via delayed cord clamping and cord milking at delivery in the setting of congenital Bart's hemoglobinopathy, and demonstrates that partial exchange transfusion of the newborn may optimize oxygen delivery due to the more favorable oxygen affinity of transfused adult hemoglobin compared with the Bart's hemoglobin.
Keywords: hemoglobin Bart; fetal transfusion; partial exchange transfusion